Analysis of an Improved Reliability Dual-Buck Structured Three-Level Flying Capacitor Inverter - Kahwa, Almachius Kamala; Mushi , Aviti Thadei (Tanzania Journal of Engineering and Technology, 2025)
<span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">With the increased demand for high-reliability power converters in the electric drive-train and propulsion systems, the efforts to design and analyze converters with high fault tolerance have become apparent. Among the emerging trends to improve the reliability of power converters is the incorporation of dual-buck (DB) structures in traditional converter topologies. Thus, this paper studies a single <span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">phase dual-buck structured three-level flying capacitor (FC) inverter. The dual-buck flying capacitor (DBFC) inverter was constructed in such a way as to suppress the shoot-through problems that may occur because of the switching mismatch and gate driver delay, as exhibited in the traditional FC inverter. The detailed operation of the DBFC inverter was performed using a comparative analysis of the traditional FC inverter as a benchmark. It was noted that the DBFC inverter considerably reduces the current stress on some switches and mitigates the shoot-through problem. Moreover, it was inferred that apart from improving the reliability of the inverter, the DBFC inverter reduces the total harmonic distortion (THD) of the output current. The 98.8% maximum efficiency and 4.03% THD were depicted in the DBFC at a switching frequency of 40 kHz. The results of the study were validated using detailed simulations and preliminary experiments.